Inhibition of epithelial-mesenchymal transition in response to treatment with metformin and Y27632 in breast cancer cell lines - Leonel, Camila [UNESP]; Ferreira, Lívia Carvalho [UNESP]; Borin, Thaiz Ferraz; Moschetta, Marina Gobbe; Freitas, Gabriela Scavacini; Haddad, Michel Raineri; Robles, João Antonio de Camargos Pinto; Zuccari, Debora Aparecida Pires de Campos [UNESP] (Bentham Science Publishers, 2017)
Background: ROCK-1 expression is associated with the malignant character of tumors, while inhibiting this molecule results in a significant suppression of tumor metastasis. Likewise, transforming growth factor beta (TGF-β) is associated with this malignancy by having the ability to induce epithelial-mesenchymal transition (EMT). Metformin, a drug used in the treatment of diabetes, has previously been shown to inhibit EMT in breast cancer cells. Objective: The aim of this study is to evaluate the TGF-β1 action model for induction of EMT and the action of metformin and ROCK-1 inhibitor (Y27632) in EMT process in breast cancer cell lines. Method: MCF-7 and MDA-MB-231 cell lines were treated with metformin and Y27632, after induction of EMT by TGF-β1, to examine the effects on cell migration as well as the protein expression of the ROCK-1 markers, vimentin, E-cadherin, CD44 and CD24 by immunocitochemistry. Results: There was a lower protein expression of ROCK-1, vimentin, CD44 and CD24 in both cell lines after treatment with metformin and Y27632. In MDA-MB-231 cells, E-cadherin expression was increased in all treatment groups. Treatment of MDA-MB-231 cell line with metformin and Y27632 significantly reduced the invasion of these cells. Conclusion: This study confirms the benefits of metformin and Y27632 as potential therapeutic agents in mammary tumors, by blocking EMT process and metastatic potential.
Keywords: Anticarcinogenic agents; Breast cancer; EMT; Metformin; ROCK1; TGF-β